The impact of cognitive impairment and possible sarcopenia on mortality - Huixia Cao; Jiefen Ou; Manzhi Gao; Yingying Zhong (Medicine, 2026)
Cognitive impairment (CI) and possible sarcopenia (PSP) are increasingly recognized as coexisting public health threats, potentially linked through shared biological mechanisms. This study used data from a U.S. prospective cohort to investigate their associations with all-cause and cardiovascular mortality. Data were obtained from the National Health and Nutrition Examination Survey 2011 to 2014 and linked to National Death Index mortality records through 2019. We examined the associations of CI and PSP with all-cause and cardiovascular mortality. PSP was defined as low muscle strength assessed by handgrip strength according to established cutoff values in the absence of direct measurements of muscle mass. Kaplan–Meier survival analyses and Cox proportional hazards models were applied to estimate mortality risks. Subgroup and sensitivity analyses were performed to evaluate the robustness of the findings. A total of 2601 participants were included and classified into 4 groups according to CI and PSP status: 894 (34.4%) CI−/PSP−, 716 (27.5%) CI+/PSP−, 334 (12.8%) CI−/PSP+, and 657 (25.3%) CI+/PSP+. Kaplan–Meier and multivariable Cox analyses showed that the CI+/PSP+ group had the highest risk of all-cause mortality ( P < .001). Compared with the CI−/PSP− group, adjusted hazard ratios were 1.82 (95% confidence interval [CI]: 1.23–2.70) for CI+/PSP−, 1.95 (95% CI: 1.25–3.03) for CI−/PSP+, and 3.41 (95% CI: 2.40–4.83) for CI+/PSP+. For cardiovascular mortality, a significantly increased risk was observed only in the CI+/PSP+ group (hazard ratio = 3.75, 95% CI: 2.45–5.19). Subgroup analyses indicated that the associations were stronger among women and individuals younger than 70 years. The concurrent presence of CI and PSP is associated with a substantially increased risk of all-cause mortality, especially among women and individuals younger than 70 years. These findings highlight the importance of early and combined screening to improve risk stratification and guide targeted health management in older adults.